Intraluminal fluid infusion in a rat jejunum ischemia/reperfusion model is associated with improved tissue perfusion and less mucosal damage - YILDIRIM, ALPER; YILMAZ, BETÜL; SAÇAK, BÜLENT; ERCAN, FERİHA; ÇELEBİLER, ÖZHAN BEKİR (ELSEVIER SCI LTD, 2020)
Objective: This study used an experimental model mimicking early postoperative enteral feeding after the transfer of free jejunal flap and tested the hypothesis that jejunal infusion with dextrose or saline is associated with improved tissue perfusion and/or less mucosal damage after ischemia/reperfusion (IR) injury. Methods: Thirty-five male Sprague Dawley rats were randomly divided into five groups: sham group (no IR and no intraluminal infusion); IR control group (IR but not intraluminal infusion); IR plus intraluminal 0.9% NaCl infusion or 5% dextrose or 10% dextrose infusion groups. A jejunal segment of each rat was isolated. The animals had jejunal ischemia for 40 min, reperfusion, and intestinal infusion on the basis of their allocation. Jejunal tissue perfusion was measured with laser Doppler flowmetry at one hour and two hours after reperfusion, after which the animals were sacrificed and tissue samples were obtained for the scoring of histological damage at superficial and cryptic epithelium, villus structure, and inflammatory cell infiltration and tissue nitric oxide (NO), interleukin (IL)-1, IL-6, and matrix metalloproteinase-1 (MMP) level measurements. Results: At 1 h of reperfusion, IR plus 5% dextrose and 10% dextrose groups both had significantly higher perfusion rates than the IR control group (384.8 +/- 26.7 and 462.4 +/- 44.7 versus 270.3 +/- 34.2 PU, respectively, p < 0.05 for both). These differences were maintained at 2 h of reperfusion (p < 0.05 for both). Saline infusion, however, resulted in improved tissue perfusion only at the early phase of reperfusion. Intraluminal infusion with dextrose solution, either 5% or 10%, was associated with higher tissue NO, IL-1, and IL-6 levels than that in the sham group (p < 0.05 for all). In addition, intraluminal infusion of any fluid resulted in less severe histo-logical damage (8.1 +/- 0.9 versus 5.8 +/- 1.0, 5.4 +/- 0.9, and 5.2 +/- 1.9, for IR plus saline, 5% dextrose and 10% dextrose groups, respectively, p < 0.05 for all). Conclusions: Intraluminal infusion of fluids, particularly dextrose solutions, may be protective against IR injury as demonstrated by improved tissue perfusion and less histological damage. In addition, increases in tissue NO, IL-1, and IL-6 levels in association with dextrose infusion may be explained by the activation of pro-inflammatory and anti-inflammatory protective pathways. These support early enteral feeding after free jejunum flap transfers; however, further studies are warranted. (C) 2019 British Association of Plastic, Reconstructive and Aesthetic Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: Intraluminal infusion; Tissue perfusion; Laser Doppler flowmetry (LDF); Nitric oxide (NO); Interleukin-1 (IL-1); Interleukin-6 (IL-6); ISCHEMIA-REPERFUSION INJURY; POSTOPERATIVE ENTERAL NUTRITION; INTESTINAL BLOOD-FLOW; GASTROINTESTINAL CANCER; SMALL-BOWEL; PROTEIN KINETICS; RECONSTRUCTION; INTERLEUKIN-6; TIME